Capillary lactate as a prognostic marker in sepsis: correlation with venous lactate and prediction of outcomes - Philip A. Joseph; Dinul Doluweera; Amalka Chandraratne; Branavan Balasubramaniam; Varuna Abeyratne; Saman P. Hewa; Roshan Rambukwella; Kamani P. Wanigasuriya; Jegarajah Indrakumar; Nilanka Perera (BMC Infectious Diseases)
Abstract Introduction Venous lactate (VL) measured by a blood‒gas analyser is not widely available despite its importance in the management of sepsis. Capillary lactate (CL) measured via a hand-held lactate analyser is a feasible and less expensive option. The aim of this study was to determine the correlation between CL and VL in sepsis patients at 0 h (t0) and 6 h (t6) and identify the best CL and lactate clearance cut-off values that predicts a poor outcome. Methods A descriptive study was conducted recruiting all patients with suspected sepsis (qSOFA ≥ 2 with evidence of infection) admitted to a tertiary care hospital in Sri Lanka between March and June 2022. “Lactate-plus”, a hand-held lactate analyser, was used to measure CL and VL at t0 and t6 of admission. The lactate analyser was tested for accuracy and calibrated in a pilot study of 30 patients by correlating to laboratory lactate values. Patient demographics, clinical data and outcomes during hospitalization and at 28 days were assessed. Results There were 102 patients with suspected sepsis and a median age of 71.5 (interquartile range: 62–77) years were recruited. Majority were females (n = 52, 51%). Majority of the source of infection was pulmonary (n = 57, 55.9%) and urological (n = 19, 18.6%). Paired CL and VL values significantly correlated at both t0 and t6 (p < 0.001). CL at t0 predicted 28-day mortality with a ROC curve AUC of 0.89 (95% CI: 0.82–0.95, p < 0.05) and 3.5 mmol/L was the best cut-off value with an 85% sensitivity and 78% specificity. CL ≥ 3.5 at t0 was associated with increased intensive care unit (ICU) admission (p < 0.01), vasopressor requirement (p < 0.0001), and a higher mortality rate (p < 0.001) compared to CL < 3.5. Additionally, a capillary lactate clearance greater than 64% predicted a good outcome, with a 97% sensitivity and 91% specificity. Conclusions CL measured by a lactate meter correlates well with VL and effectively predicts sepsis outcomes. A CL cut-off ≥ 3.5 mmol/L at admission increases the risk of mortality, vasopressor requirement and ICU admission, making CL a useful tool for risk assessment in sepsis.